SYSTEMIC LUPUS ERYTHEMATOSUS: CLINICAL RECOMMENDATIONS. PART 2 - Ekaterina I. Alexeeva; Tatiana M. Dvoryakovskaya; Irina P. Nikishina; Rina V. Denisova; Nadezhda S. Podchernyaeva; Ol'ga A. Sukhorukikh; Lyubov' S. Shubina; Vyacheslav G. Chasnyk; Mikhail M. Kostik ("Paediatrician" Publishers LLC, 2018)
The article presents modern ideas about the treatment of systemic lupus erythematosus (SLE). The details of the management of patients with SLE during immunosuppressive and genetically engineered therapy is given. The article also reflects the aspects of rehabilitation, prevention of exacerbations, and follow-up care of children with SLE. The criteria for assessing the quality of medical care for children with SLE are presented. The detailed information on systemic lupus erythematosus for patients with SLE and their parents is outlined specifically.